Effects of pilates training on muscular strength and balance in ballet dancers - Amorim, T.; Sousa, F.; Machado, L.; Santos, J. A. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to determine the effects of a Pilates training programme on muscular strength and balance in ballet dancers. Fifteen ballet students were divided in experimental and control groups. Besides the daily technical classes, it was applied a Pilates training programme during 11 weeks in the experimental group. Groups were submitted at two moments of evaluation, before and after the programme. The muscular strength was evaluated through the time obtained in the maintenance of the performance of penché and developpé. Balance was evaluated using a Bertec force plate (4060-15). The migration area of the centre of pressure was calculated in the first position and in the attitude derriére skills. Results suggest that the Pilates training have a positive effect on muscular strength. No significant differences were obtained in ballet dancers' balance.